1 - La Question démocratique dans le tiers monde contemporain* - Amin, Samir (Africa Development, 1989)
The recent past is marked by global movements to democratize political regimes. In socialist countries, the movement forced regimes to take it into account, adopt to its exigen- cies or perish. Although it has not reached the same popular dimension, in third world capitalist countries, the demand for democracy signals a qualitative leap in the penetration of democratic consciousness. Simultaneously, one finds the rise of neo-liberalism, a generalized offensive ai- med at the rehabilitation of the absolute superiority of private property, the legitimization of social inequalities and anti-statism. Neo-liberalism has no frontiers. Orchestrated by an unprece- dented media campaign it unilaterally asserts that "the market" - a euphemism for capitalism is the central axis to any "development". Democratization is considered as the necessary and natural product of the submission to the rationality of the worldwide market. A simple double equation is deduced from this logic: capitalism = democracy, democracy = capitalism. The focus is on technical and scientific progress whereas the social realities which hide behind "the market forces" are systematically occulted. The present offensive of Western countries "in fa- vour of democracy" is in fact an offensive against socialism. Similarly "national liberation" is proclaimed obsolete; "nationalism" is accused of necessarily engendering a deadly delay in the international competition. There is no need to denigrate the heritage of Western bourgeois de- mocracy. But the dominant contemporary perspective marked by Anglo-Saxon evolutionism and pragmatism empoverishes the debate by reducing democracy as a set of precise and limited rights and practices independent from the desired social perspectives. What type of democracy do we need?